(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Sorghum (Sorghum bicolor [L.] Moench) is the fifth most widely cultivated cereal grain globally. It is valued for its rich nutritional profile, gluten-free nature, and health-promoting properties, particularly its antioxidant potential. However, limited comparative data exist on the nutritional content, phytochemicals, and antioxidant activities between the red and white sorghum. This research aims to compare these characteristics between the two variants of sorghum, which is red sorghum and white sorghum. Red and white sorghum were dehydrated at 60 °C for 1 hour. Proximate analysis was performed to determine the nutritional content, Folin-Ciocalteu assay for total phenolic content (TPC) and aluminum chloride colorimetric method for total flavonoid content (TFC). Antioxidant activities were assessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH+) and 2,2’-azino-bis [3-ethylbenzothiazoline-6-sulfonic acid] (ABTS+) assays. The results were analyzed using one-way analysis of variance (ANOVA), and differences with p < 0.05 were considered statistically significant. Red sorghum exhibited significantly higher protein (p = 0.001), while white sorghum exhibited higher ash content (p = 0.036). Although red sorghum showed slightly higher TPC (235.03 ± 59.82 µg GAE/g) and TFC (6.53 ± 3.27 µg QE/g) than white sorghum (214.03 ± 74.08 µg GAE/g and 4.95 ± 2.8 µg QE/g, respectively), the differences were not statistically significant (p > 0.05). The DPPH assay showed that WS exhibited significantly higher radical scavenging activity with 87.4% inhibition (IC₅₀ = 260.01 µg/ml) compared to RS at 77.4% inhibition (IC₅₀ = 268.67 µg/ml). Conversely, the ABTS assay revealed stronger antioxidant activity in RS, which had a higher inhibition percentage (67.6%, IC₅₀ = 326.00 µg/ml) than WS (49.0%, IC₅₀ = 827.27 µg/ml), indicating cultivar-dependent differences in antioxidant efficacy. Thus, red and white sorghum each exhibit distinct strengths, with significant differences in protein, ash content and free radical inhibitions (DPPH and ABTS). However, their comparable TPC, TFC suggest equal potential for functional food applications.